2004
DOI: 10.1104/pp.104.051623
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Dynamics and Differential Microtubule-Binding Activities of MAP65 Proteins

Abstract: Plant cells produce different microtubule arrays that are essential for cell division and morphogenesis without equivalent in other eukaryotes. Microtubule-associated proteins influence the behavior of microtubules that is presumed to culminate into transitions from one array to another. We analyzed the microtubule-binding properties of three Arabidopsis (Arabidopsis thaliana) members, AtMAP65-1, AtMAP65-4, and AtMAP65-5, in live cells using laser scanning confocal microscopy. Depending on the overall organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
151
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 160 publications
(166 citation statements)
references
References 45 publications
7
151
3
Order By: Relevance
“…Typically, during interphase CMTs were decorated with GFP-AtMAP65-5 (Van Damme et al, 2004a). We found that during prophase, GFPAtMAP65-5 strongly labeled the preprophase band, a hallmark for the division zone, and the perinuclear MTs before the initiation of the bipolar spindle ( Figure 7A, Video S1).…”
Section: Atmap65-5 Localization During Mitosismentioning
confidence: 85%
See 4 more Smart Citations
“…Typically, during interphase CMTs were decorated with GFP-AtMAP65-5 (Van Damme et al, 2004a). We found that during prophase, GFPAtMAP65-5 strongly labeled the preprophase band, a hallmark for the division zone, and the perinuclear MTs before the initiation of the bipolar spindle ( Figure 7A, Video S1).…”
Section: Atmap65-5 Localization During Mitosismentioning
confidence: 85%
“…AtMAP65-6 colocalizes with mitochondria (Mao et al, 2005b). Finally, AtMAP65-5 associates with a subset of transversely organized CMT bundles in interphase as well as the phragmoplast during cytokinesis (Van Damme et al, 2004a). On the basis of the their diverse localization patterns, we postulate that AtMAP65s exhibit differential molecular and functional properties which still remain to be identified.…”
mentioning
confidence: 93%
See 3 more Smart Citations